Praktik Stoikisme sebagai Strategi Koping Akademik dalam Perspektif Islam: Studi pada Mahasiswa di Perguruan Tinggi Muhammadiyah - Mardhatillah L. Rauf; Naufal Ahmad Rijalul Alam (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
This study aims to explore the application of Stoic values as an academic coping strategy from an Islamic perspective among Islamic Religious Education (PAI) students at Muhammadiyah University of Yogyakarta. The study employed a descriptive qualitative approach using purposive sampling of six students. Data were collected through semi-structured interviews and analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and concluding. The results indicate that PAI students integrate Stoic principles, such as the dichotomy of control, premeditatio malorum, amor fati, and memento mori, into the framework of Islamic values conceptually, practically, and emotionally. These principles are interpreted in harmony with the concepts of ikhtiar, tawakal, sabar, as well as qada and qadar, in coping with academic stress. This integration contributes to the development of academic resilience and adaptive emotional regulation. However, the study also found variations in understanding and implementation challenges, such as a tendency toward fatalistic interpretations and a gap between conceptual understanding and actual practice. Furthermore, the practice of premeditatio malorum among some students may trigger anxiety if not accompanied by appropriate cognitive regulation. Therefore, reflective guidance and institutional support are needed to optimize the integration of Stoic values and Islamic teachings in Islamic Education (PAI) learning. This study contributes to the development of a values-based learning approach to enhance students’ resilience and psychological well-being.